BONE DENSITY GROWTH. BIOMECHANICS OF HEALTHY AND PROSTHETIC FEMUR AFTER A TOTAL HIP ARTHROPLASTY - O'Connor, Joan; Borges, Lavinia Maria Alves; Duda, Fernando Pereira; Cruz, Antonio Guilherme Barbosa da (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The necessity of computational tools to predict the long-term behavior of bone implants and prosthetic devices in orthopedics, has a tremendous importance, considering population aging as a world wide problem. However, specifically in the hip prosthesis research area, the bone density growth process modeling using the finite element method (FEM) is still a challenging task. In this work, we investigate the bone density growth based on growth and remodeling theories for biological materials and its treatment using continuum mechanics. There are presented the kinematics, the balance laws for mass and linear momentum and the constitutive equations for bone density growth, along with the governing equations resulting from the coupling of the mass and momentum balances. We present an example considering the healthy and the prosthetic femur submitted to loads and bone formed by cortical and spongious tissues, which was carried out using daily physical activities load cases, for locate possible growth and resorption. In addition, a preliminary density growth model to locate bone growth or reabsorption zones for the intact femur and its post-operative condition is presented.